Therapeutic Efficacy of Silver Nanoparticles in Clinical Endometritis Affected Buffaloes - Mallika, Mulagapaka; Rao, Kondareddy Prabhakar; Prasad, Borra Chandra; Rao, Chitirala Mallikarjuna (Indian Journal of Veterinary Sciences and Biotechnology, 2026)
Bacterial invasion of the uterus during the postpartum period is a leading cause of clinical endometritis in dairy cattle and buffaloes. Excessive use of antibiotics has led to bacterial resistance, prompting the need for alternative therapies. Sixteen buffaloes diagnosed with clinical endometritis confirmed through detailed clinico-gynecological examination were selected for the current study and were divided into two groups of eight each. Group I (n=8) received intrauterine administration of 4 mg silver nanoparticles in 20 mL PBS for three consecutive days, while Group II (n=8) received a single dose of 100 µg E. coli LPS in 20 mL PBS. These animals were evaluated for haemato-biochemical parameters before and after treatment, which revealed significant reduction (p<0.05) in serum creatinine kinase at subsequent estrus post-treatment in both the groups. Haemoglobin and PCV increased non-significantly (p>0.05), whereas serum BUN decreased non-significantly at subsequent estrus after treatment. The recovery and conception rates were 75.0% and 66.7% in Group I and 85.5% and 71.4% in Group II, respectively, which did not differ significantly. Based on the present study, Silver nanoparticles are proved to be effective in managing clinical endometritis, demonstrating similar recovery and conception rate to those of E. coli LPS, thereby serving as a promising alternative to antibiotic therapies.